Mechanisms of organelle elimination for lens development and differentiation. (August 2021) - Brennan, Lisa; Disatham, Joshua; Kantorow, Marc
Abstract: A hallmark feature of lens development and differentiation is the complete elimination of organelles from the center of the eye lens. A long unanswered question in lens biology is what are the mechanisms that control the elimination of organelles during the terminal remodeling program to form mature lens fiber cells? Recent advances have expanded our understanding of these mechanisms including newly discovered signaling pathways, proteasomal regulators, autophagy proteins, transcription factors and the hypoxic environment of the lens itself. These recent discoveries suggest that distinct mechanisms coordinate the elimination of the nucleus, mitochondria, endoplasmic reticulum and Golgi apparatus during lens fiber cell differentiation. Since regulation of organelle number and distribution is also a feature of the terminal remodeling programs of more complex cell-types and tissues, these advances are likely to impact a wide-variety of fields. Highlights: Lens differentiation is hallmarked by the elimination of cellular organelles. Novel pathways have recently been identified that coordinate lens organelle elimination. Lens organelle elimination requirements include signal-transduction, autophagy and hypoxia.